Technical and socioeconomic evaluation of a ride-on tillage implement for the hand tractor - Bautista, Elmer G. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
The ride-on tillage implement can accomplish all major land preparation operations such as levee-side plowing, plowing, harrowing and leveling. Its technical performance was evaluated under actual field conditions while a socioeconomic evaluation was done through a structured questionnaire to gather feedback on its acceptability. The average travel speeds during side plowing, ride-on plowing, harrowing and leveling were 2.4, 3.6,3.7 and 3.2 km h -1, respectively. The field capacities during side plowing, plowing, harrowing and leveling were 0.71 ha h-1 (approximately 2110 m ha -1), 0.2 ha h-1,0.41 ha h-1 and 0.41 ha h -1, respectively; and the machine efficiencies 96.5%, 84.8%, 84.9% and 84.1%, respectively. One half hectare could be completely prepared within an 8-h day. The operation time to finish a certain area was distributed as follows: side plowing (9%), plowing (34%), 1st harrowing (22%), 2nd harrowing (13%) and leveling (22%). All respondents were hand tractor users, however, 36% still used the carabao for selected operations. Respondents were satisfied with the investment cost and the safeness of operation. Ninety-seven percent of them wanted to own an implement at PhP 5,600 per unit. The ride-on tillage implement can generate a net income of PhP 39,527.9 per yr. The investment cost could be returned in 1.9 yr after having prepared 57 ha.